Epidemiology of gaming disorder and its effect on anxiety and insomnia in Chinese ethnic minority adolescents - Qiaoyue Wei; Shengjie Zhang; Yuli Pan; Hong Hu; Fenglan Chen; Wenwen Yin; Qinghong Lin; Shuibo Pan; Chingyuan Tham; Junduan Wu (BMC Psychiatry, 2022)
Abstract Background The growing popularity and frequency of online game use have resulted in a large number of studies reporting various mental problems associated with game abuse in adolescents. In this article, we examined the prevalence of gaming disorder (GD) and explored the associations of GD with anxiety and insomnia symptoms in minority youth in China. Methods A total of 1494 students completed the Problematic Online Gaming Questionnaire Short-Form (POGQ-SF), the Generalized Anxiety Disorder 7-item questionnaire (GAD-7), and Athens Insomnia Scale (AIS). Chi-square and binary logistic regression analyses were used to explore the associations between gaming disorder and anxiety/insomnia. Results A total of 356 (23.83%) respondents reported that they had gaming disorder. Chi-square analysis showed that gender, grade, marital status of parents and exercise situation were significantly associated with GD. Binary logistic regression analysis showed that those who had GD were at significantly higher risk for anxiety and insomnia than those without GD. Conclusion We found a high incidence of GD and a positive association among anxiety, insomnia and GD. Thus, special attention should be paid to those who have suffered from GD. It is worth addressing the adverse effects of GD on anxiety and insomnia.